Turkish translation and validation of the Xerostomia Inventory - Sezin Yüce Sarı; Melek Tuğce Yılmaz; Ayşenur Elmalı; Levent Kılıç; Deniz Yüce; Gökhan Özyiğit; Mustafa Cengiz; Gözde Yazıcı (Archives of Rheumatology, 2022)
Objectives: The Xerostomia Inventory (XI) was developed to assess the severity of dryness in patients with xerostomia. It has a long and a short form with three- and five-point Guttman-type response options. In this study, we aimed to translate the XI into Turkish, to assess the validity and reliability of both response options in patients with head & neck cancer (HNC) or Sjögren syndrome (SS), and to select the optimal version for Turkish patients. Patients and methods: Between January 2019 and June 2019, the XI was translated into Turkish (XI-T) and applied to patients aged ≥18 years with HNC and SS. All patients were applied two tests including both the three- and five-point options. The internal consistency was assessed by Cronbach alpha and test-retest reliability by intraclass correlation coefficients (ICCs). Content validity was based on expert opinion and patient reviews. Results: A total of 186 patients (109 males, 77 females; median age: 54 years; range, 19 to 78 years) answered the XI-T. The number of patients with HNC and SS was 143 (77%) and 43 (23%), respectively. Median XI-T score was 17 for the three-point, and 24 for the five-point option, respectively. Overall internal consistency was satisfactory for both options (α=0.81 and α=0.89, respectively). Overall test-retest reliability was satisfactory and ICCs ranged between 0.71 and 0.92 for the three-point, and 0.36 and 0.94 for the five-point option, respectively. Assessments based on expert opinions and patient reviews also favored the content validity of the scale. Conclusion: The XI-T with both three- and five-point options is a valid and reliable tool to evaluate the presence and severity of dryness in patients with HNC and SS who experience xerostomia. The three-point option is more comprehensible and can be preferred over the five-point option in the Turkish population.